Typology of Hadith Madrasas in Mecca and Their Figures - Sarah Fauziah (al-Afkar, Journal For Islamic Studies, 2026)
Hadith scholars are encouraged to guard and preserve hadith from generation to generation because of its very important position and function in Islamic teachings. This guarding and preservation began during the time of the Companions and continues to this day. It was the Companions and senior tābi'īn who first spread to various regions and organized scientific circles (ḥalaqah) throughout the region to help spread hadith. This community is called “Hadith Madrasah” by contemporary hadith researchers. This article aims to discuss “Hadith Madrasah,” starting from the definition, urgency, and technical steps of its study, as a reference for researchers who are interested in conducting this study. This research is a type of qualitative research using historical methods. The approach used is descriptive-analytical with data collection techniques using library research. The results of this study indicate that the Hadith Madrasah is a "community of narrators and hadith experts with the same characteristics between one member and another, related to the media for conveying and maintaining hadith, both riwāyah and dirāyah, at a certain time and place. Anyone who wants to investigate the Hadith Madrasah must follow at least six technical steps.